Ride the river : a novel - L'Amour, Louis, 1908-1988 (L'Amour, Louis, 1908-1988. Sacketts., 2021)
Young Echo Sackett, who is a sure hand with a horse, a dead shot with a rifle, and fast with her wits, travels to the mountains of Tennessee, where she encounters ruthless killers who will stop at nothing to cheat her of her inheritance.